“When I need help, I ask my friends”: experiences of Spanish autistic women when disclosing their late diagnosis to family and friends - Garcia-Molina, Irene (Frontiers in Psychology, 2024)
Family and friends play an important role in the initiation and process of diagnosing autism -as well as in supporting them afterwards. However, when the diagnosis arrives late, as is often the case with autistic women, we find the double stigma of experiencing the repercussions of a late diagnosis, compounded by the disbelief of those closest to them. This study aims to analyse and learn about the experiences of autistic women with their family and friends derived from the diagnostic process and later help-seeking. A total of 21 Spanish autistic women aged between 20 and 58 answered a series of open-ended questions-respecting the participants' preferred modality. From the thematic analysis, two main themes emerged regarding the reactions of family and friends, dividing the experiences into two moments in time: when disclosing the diagnosis and sometime later. Most participants noted that their relatives did not believe them, reacted in a hostile way, or did not give it any importance at the time of disclosure. As a result, their relationship deteriorated even further after a time. In contrast, their friends served as pillars of support from the start, along with their partners and associations they attended, thanks to which they met more autistic women who became their 'family' now. Thus, another consequence of late diagnosis in autistic women is highlighted, the incomprehension or disbelief of their relatives; as well as the important role of friendships between women, and between autistic women.